Kraft Pulping of Leucaena leucocephala - Bhola, P. P.; Sharma, Y. K. (Indian Forester, 1982)
Laboratory Investigation reveals the potentiality of Leucaena leucocephala, a fast growing species commonly cultivated to have diverse uses such as, firwood, timber, nutritious forage, dye, gum and rich organic fertilizer, for pulp and paper making to supplement the existing raw material resource. Leucaena wood has bigh holocellulose, low ash and solubilities. Unbleacbed kraft pulp. With about 48-56% yield can be produced with low active alkali (12-16% at 170Â°C for 150-240 minutes. The pulp with 14% active alkali and 2430 H -factor can be bleached to 70% ISO brightness with 10% chlorine by C/E/H sequence and Is suitable for writing and printing papers. The black liquor has good colloidal stablity during evaporation and burning properties.